Mucin-Like Domain of Mucosal Addressin Cell Adhesion Molecule-1 Facilitates Integrin α4β7-Mediated Cell Adhesion Through Electrostatic Repulsion - Yuan, MengYa; Yang, YanRong; Li, Yue; Yan, ZhanJun; Lin, ChangDong; Chen, JianFeng (Frontiers in Cell and Developmental Biology, 2020)
The homing of lymphocytes from blood to gut-associated lymphoid tissue is regulated by interaction between integrin α4β7 with mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1) expressed on the endothelium of high endothelial venules (HEVs). However, the molecular basis of mucin-like domain, a specific structure of MAdCAM-1 regulating integrin α4β7-mediated cell adhesion remains obscure. In this study, we used heparan sulfate (HS), a highly acidic linear polysaccharide with a very variable structure to mimic the negative charges of the extracellular microenvironment and detected the adhesive behaviors of integrin α4β7 expressing 293T cells to immobilized MAdCAM-1 in vitro. The results showed that HS on the surface significantly promoted integrin α4β7-mediated cell adhesion, decreased the percentage of cells firmly bound and increased the rolling velocities at high wall shear stresses, which was dependent on the mucin-like domain of MAdCAM-1. Moreover, breaking the negative charges of the extracellular microenvironment of CHO-K1 cells expressing MAdCAM-1 with sialidase inhibited cell adhesion and rolling velocity of 293T cells. Mechanistically, electrostatic repulsion between mucin-like domain and negative charges of the extracellular microenvironment led to a more upright conformation of MAdCAM-1, which facilitates integrin α4β7-mediated cell adhesion. Our findings elucidated the important role of the mucin-like domain in regulating integrin α4β7-mediated cell adhesion, which could be applied to modulate lymphocyte homing to lymphoid tissues or inflammation sites.